Finite element analysis of 3d steel jacket frame (offshore structure) using ANSYS - Tengku Muhammad Hasif, Tengku Mohamed Salim (2015)
Jackets were among the very first structures that used in the offshore industry, as stable platforms mainly for oil and gas production facilities. Frame is one of the important elements of this structure. Unfit or improper design can lead to the failure of a structure. The steel jacket frame was analyzed by manual calculation and also design in ANSYS software. There are several methods can be used to analyses the behaviour of steel jacket frame. However, among all these methods, finite element method and probabilistic method will be a very effective method to obtain the strength and behaviour of steel structure. This analysis is to determine the behaviour of frame design for the jacket structure. This research will mainly focus on the steel frame of jacket platform. The yield strength of steel jacket that used is 500 N/